PENGARUH TINGKAT HUTANG DAN ARUS KAS AKRUAL TERHADAP PERSISTENSI LABA (STUDI PADA PERUSAHAAN PROPERTY AND REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2010-2014) - Nurul Fitriana; Wida Fadhlia (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2016)
This research examines the influence of leverage and accrual cash flow to the earnings persistence on property and real estate companies listed in Indonesia Stock Exchange in 2010-2014. The research type used in this research is hypothesis testing, by using purposive sampling method and there are 150 samples to be analized of data that become the object to be researched.The data type used is secondary data obtained from the financial statements ended on 31 December, published by the capital market reference center in the Indonesia Stock Exchange. The analysis used is multiple linear regression to test the hypothesis.The results of this research are leverage and accruals cash flow simultaneously have an effect on earnings persistence. Leverage has a significant influence toward earnings persistence, nevertheless Accruals Cash Flow does not have influence toward earnings persistence.  Keywords— Leverage, Accruals Cash Flow and Earnings Persistence.